The Relationship Between Anxiety and Events Chemotherapy-Induced Nausea Vomiting (CINV) Breast Cancer Patients with Chemotherapy in Jember, East Java, Indonesia - Siti Mu'awanah; Ahsan Ahsan; Heni Windarwati (Jurnal Kesehatan dr. Soebandi, 2024)
In Indonesia and worldwide, breast cancer accounts for the greatest number of cancer patients. Chemotherapy is the treatment used to treat breast cancer patients; however, it might cause One of the psychological adverse effects that chemotherapy usually causes for individuals with breast cancer is anxiety. Chemotherapy-Induced Nausea Vomiting (CINV) is the most common physical adverse effect experienced by breast cancer patients receiving chemotherapy. This cross-sectional study employs certain research approaches. Patients receiving chemotherapy for breast cancer at the RSD Dr. Soebandi Jember and Baladhika Husada Jember Hospital made up the study's population. This research was conducted for one month, and the number of samples used in this research was 120. Anxiety measurement uses a questionnaire Hamilton Anxiety Rating Scale (HAM-A) to measure levels of anxiety, and the Multinational Association of Supportive Care in Cancer (MASCC) Antiemesis Tool (MAT) to measure Chemotherapy Induces Nausea and Vomiting (CINV). Data analysis with a paired sample t test using the IBM SPSS v.25 for Windows programme. The results of the Pearson correlation test between anxiety and CINV in breast cancer patients undergoing chemotherapy showed a significance value of 0.00 or <0.05, which means there is a correlation between anxiety and CINV experienced by respondents. The higher the level of anxiety, the more CINV complaints the patient will experience. Vice versa, the lower the level of anxiety, the CINV experienced by the patient will be minimal. Keyword: anxiety, CINV, Breast Cancer, Chemotherapy